Assembling the Reclaimer for Utilization of the Air with Ultraviolet - Mikayeva, S.A. (International Journal of Engineering and Technology, 2018)
The article presents a re-circulator designed for disinfecting air with ultraviolet light. Disinfection of air in the re-circulator is due to the impact on microorganisms of bactericidal UV radiation with a wavelength of 254 nm. Inactivation of microorganisms occurs due to the message sent to them of a sufficient dose of UV irradiation. The technical characteristics of AEROLIT - 550 re-circulators are described. The assembly and the re-circulator device are described. The re-circulator is designed for disinfecting air with UV radiation in the premises of the food industry, catering and trade, as well as in production workshops, warehouses, storage of finished products and raw materials, public places, where the characteristics of the re-circulator do not contradict the requirements for the above places, in the presence of people.